The unconventional Xer recombination machinery of Streptococci/Lactococci. - Pascal Le Bourgeois; Marie Bugarel; Nathalie Campo; Marie-Line Daveran-Mingot; Jessica Labonté; Daniel Lanfranchi; Thomas Lautier; Carine Pagès; Paul Ritzenthaler (PLoS Genetics)
Homologous recombination between circular sister chromosomes during DNA replication in bacteria can generate chromosome dimers that must be resolved into monomers prior to cell division. In Escherichia coli, dimer resolution is achieved by site-specific recombination, Xer recombination, involving two paralogous tyrosine recombinases, XerC and XerD, and a 28-bp recombination site (dif) located at the junction of the two replication arms. Xer recombination is tightly controlled by the septal protein FtsK. XerCD recombinases and FtsK are found on most sequenced eubacterial genomes, suggesting that the Xer recombination system as described in E. coli is highly conserved among prokaryotes. We show here that Streptococci and Lactococci carry an alternative Xer recombination machinery, organized in a single recombination module. This corresponds to an atypical 31-bp recombination site (dif(SL)) associated with a dedicated tyrosine recombinase (XerS). In contrast to the E. coli Xer system, only a single recombinase is required to recombine dif(SL), suggesting a different mechanism in the recombination process. Despite this important difference, XerS can only perform efficient recombination when dif(SL) sites are located on chromosome dimers. Moreover, the XerS/dif(SL) recombination requires the streptococcal protein FtsK(SL), probably without the need for direct protein-protein interaction, which we demonstrated to be located at the division septum of Lactococcus lactis. Acquisition of the XerS recombination module can be considered as a landmark of the separation of Streptococci/Lactococci from other firmicutes and support the view that Xer recombination is a conserved cellular function in bacteria, but that can be achieved by functional analogs.